SOLUSI CERDAS UNTUK PENGELOLAAN SAMPAH PLASTIK MELALUI PELATIHAN ECOBRICK DI DESA JIKEN KECAMATAN TULANGAN - Risdiana Chandra Dhewy (STKIP PGRI Sidoarjo, 2020)
Community service activities by STKIP PGRI Sidoarjo Student Community Service Team were carried out in Jiken Village, Tulangan, Sidoarjo. This activity is carried out every year in a different location. The KKN team was attended by 6th semester students from 4 study programs, namely mathematics, history education, English language education, PGSD. Community service activities in the form of plastic waste processing solutions through ecobrick training. Ecobricking is a simple technique of using clean, dry plastic to put it in a plastic bottle until it is completely solid so that it becomes building bricks. The purpose of this activity is to create and develop insight into ecobricks and increase awareness of loving the environment. With this research, it is hoped that it can foster the creativity of the people of Jiken Tulangan in the use of used bottles in their surroundings. This activity was attended by villagers and youth organizations in Jiken Village. Based on the results of these activities, it shows that there is interest or positive response by the Jiken village community to try to apply ecobrick techniques. This can be seen from the discussion activities or questions raised by the participants regarding the use of plastic waste and used bottles in order to reduce plastic waste that can pollute their environment. Keywords: ecobrick, trash and plastic bottles.